2014
DOI: 10.1155/2014/916189
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Sputtered Gallium and Aluminum Codoped Zinc Oxide Films for Organic Solar Cells

Abstract: Gallium and aluminum codoped zinc oxide (GAZO) films were deposited at different temperatures by in-line sputtering. Aluminum is thermally unstable compared to other elements in GAZO films. The grains of GAZO films increase with deposition temperature. Coalescence between grains was observed for GAZO films deposited at 250°C. The deposition temperature exhibits positive influence on crystallinity, and electrical and optical properties of GAZO films. The carrier concentration and mobility of GAZO films increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Few reports were found using GAZO films as the electrode of OPV devices. Before, our group applied the as-deposited GAZO films as the electrode of OPV devices when the GAZO films were deposited at 250°C [ 27 ]. The as-deposited, vacuum-annealed, and hydrogen microwave plasma-annealed GAZO films were used as the electrode to replace ITO in fabricating hybrid OPV devices in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports were found using GAZO films as the electrode of OPV devices. Before, our group applied the as-deposited GAZO films as the electrode of OPV devices when the GAZO films were deposited at 250°C [ 27 ]. The as-deposited, vacuum-annealed, and hydrogen microwave plasma-annealed GAZO films were used as the electrode to replace ITO in fabricating hybrid OPV devices in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in the diffraction angle position can be attributed to the substitution of Zn 2+ ions by Al 3+ and Ga 3+ ions [21,28] and H2 occupied in the Zn-O bond center [32,33]. The (002) diffraction peaks shifted to low angles.…”
Section: Resultsmentioning
confidence: 97%
“…Post-annealing has been shown to improve the electrical and optical properties of as-deposited AZO/ITO films and reduce emissivity. In addition, our research team reported the effects of substrate temperature, vacuum annealing and hydrogen plasma annealing, respectively, on the structure and electrical and optical properties of GAZO films [28,30,31]. According to previous reports, the processing time of hydrogen plasma treatment can affect the structure of GAZO films and thus their physical properties [30,31].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Al dopant is easily oxidized during film growth because of its high reactivity, whereas the Ga dopant is more stable and resists oxidation [ 3 ]. In particular, the ionic and covalent radii of Ga are 0.62 and 1.26 Å, respectively, which are close to those of Zn (0.74 and 1.31 Å) [ 4 ]. Doping Ga in Al-doped ZnO (AZO) could reduce crystal deformation, resulting in higher crystallinity and enhanced electron transport [ 5 ].…”
Section: Introductionmentioning
confidence: 99%